The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1515/hepo-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Terminalia chebula Retz. – an important medicinal plant

Abstract: Summary Ayurveda, whispered to be the ancient practice of healthcare existed and contributes a holistic approach to health, healing and longevity. Terminalia chebula Retz. is a popular plant and widely spread all over southern Asia. T. chebula is a native plant of India and its dried fruit is extensively used in various types of home remedies. Dried fruit of T. chebula contains high quantities phenolic compounds that consist of ellagic acid, gallic acid and chebulic acid. The fruit extract of T. chebula i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Our observations indicate that DPK alleviates oxidative stress and prohibits inflammatory response. R. communis ( Abdul et al, 2018 ), T. chebula ( Bag et al, 2013 ; Kolla et al, 2018 ), T. ammi ( Ranjan et al, 2011 ; Bairwa et al, 2012 ), W. somnifera ( Dar et al, 2016 ), A. speciosa ( Joseph et al, 2011 ), C. deodara ( Gupta et al, 2011 ), V. negundo ( Gill et al, 2018 ), N. arbor-tristis ( Hussain and Ramteke, 2012 ), T. cordifolia ( Ghosh and Saha, 2012 ; Khan et al, 2016 ), C. fistula ( Kumar et al, 2017 ; Pawar et al, 2017 ), C. sativum ( Mahendra and Bisht, 2011 ; Rajeshwari and Andallu, 2011 ), F. vulgare ( Rahimi and Ardekani, 2013 ), Z. officinale ( Shakya, 2015 ), S. indicum ( Sharma et al, 2017 ), and S. surattense ( Tekuri et al, 2019 ) are rich in phytochemicals having high antioxidant potentials. G. herbaceum ( Khaleequr et al, 2012 ) has antioxidant property, whereas P. retrofractum ( Kubo et al, 2013 ) has shown to have neurotrophic effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observations indicate that DPK alleviates oxidative stress and prohibits inflammatory response. R. communis ( Abdul et al, 2018 ), T. chebula ( Bag et al, 2013 ; Kolla et al, 2018 ), T. ammi ( Ranjan et al, 2011 ; Bairwa et al, 2012 ), W. somnifera ( Dar et al, 2016 ), A. speciosa ( Joseph et al, 2011 ), C. deodara ( Gupta et al, 2011 ), V. negundo ( Gill et al, 2018 ), N. arbor-tristis ( Hussain and Ramteke, 2012 ), T. cordifolia ( Ghosh and Saha, 2012 ; Khan et al, 2016 ), C. fistula ( Kumar et al, 2017 ; Pawar et al, 2017 ), C. sativum ( Mahendra and Bisht, 2011 ; Rajeshwari and Andallu, 2011 ), F. vulgare ( Rahimi and Ardekani, 2013 ), Z. officinale ( Shakya, 2015 ), S. indicum ( Sharma et al, 2017 ), and S. surattense ( Tekuri et al, 2019 ) are rich in phytochemicals having high antioxidant potentials. G. herbaceum ( Khaleequr et al, 2012 ) has antioxidant property, whereas P. retrofractum ( Kubo et al, 2013 ) has shown to have neurotrophic effects.…”
Section: Discussionmentioning
confidence: 99%
“…G. herbaceum ( Khaleequr et al, 2012 ) has antioxidant property, whereas P. retrofractum ( Kubo et al, 2013 ) has shown to have neurotrophic effects. Indeed, T. cordifolia ( Ghosh and Saha, 2012 ; Khan et al, 2016 ) and T. chebula ( Bag et al, 2013 ; Kolla et al, 2018 ), in addition to antioxidative property, have anti-inflammatory and immunomodulatory activities. R. communis is both an antioxidant and anti-inflammatory agent ( Abdul et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The fruit pericarp of Terminalia chebula showed Cytoprotective activity, cardio tonic activity, anti-mutagenic activity and antifungal properties. 15,16…”
Section: Triphala Churna and Its Compositionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), about 80% of the world population depends mainly on plant-based traditional medicine for their primary healthcare requirement 2 When screening a number of herbal medicinal plants, scientists were discovered that T. chebula (Combretaceae) is one of the most revered medicinal plants, possesses several medicinal values due to the presence of many kinds of phytochemical constituents. T. chebula has been extensively used in ayurvedic, Unani & homoeopathic medicine and has become the cynosure of modern medicine 3 T. chebula possesses a wide variety of activities like antimicrobial 4 , antioxidant 5 , anti-viral 6 , anticarcinogenic 7 , hypocholesterolemic 8 , radioprotective 9 , anti-spasmodic and anti-purgative 10 .…”
Section: Introductionmentioning
confidence: 99%